IMPLEMENTASI PENDIDIKAN INKLUSIF BAGI ANAK BERKEBUTUHAN KHUSUS (ABK) DALAM SEKOLAH DASAR INKLUSI NEGERI DAN SWASTA DI KECAMATAN DENPASAR BARAT KOTA DENPASAR - Nurcahyani, Dwi; Sastra Wijaya, Komang Adi; Winaya, I Ketut (CITIZEN CHARTER, 2020)
ABSTRACT Inclusive education is education intended for children who have disabilities and the ability of intelligence to get educational services with student in general. Inclusive education in West Denpasar Subdistrict has been carried out by 4 elementary schools.Implementation of inclusive education in public and private elementary schools have differences in their application. The implementation of inclusive education in public elementary schools is still not optimal when compared to the implementation of inclusive education in private elementary schools, because there are no teacher assistants in public elementary schools and the assistance provided by the government is still not optimal. Keywords :Public policy, public implementation, inclusive education in Denpasar city